2015
DOI: 10.1063/1.4935451
|View full text |Cite
|
Sign up to set email alerts
|

Torsional wave propagation in a circular plate of piezoelectric radial phononic crystals

Abstract: Piezoelectric rings are periodically introduced and inserted in a base plate along the radial direction, forming a one-dimensional circular plate of piezoelectric radial phononic crystals (CPPRPC). The transfer matrix of the torsional wave between adjacent units is derived in cylindrical coordinates. Then, by introducing Lyapunov exponents, the phenomenon of the torsional wave band gap is analyzed with consideration of outer control. Furthermore, the effects of some factors, namely, radial span ratio, inner ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Ma et al (2014) studied the band structures of bilayer radial phononic crystal plate with crystal gliding. Shu et al (2015) analyzed the torsional vibration of piezoelectric radial phononic crystal plate. The effects of structural and piezoelectric parameters on the band gaps were also discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al (2014) studied the band structures of bilayer radial phononic crystal plate with crystal gliding. Shu et al (2015) analyzed the torsional vibration of piezoelectric radial phononic crystal plate. The effects of structural and piezoelectric parameters on the band gaps were also discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…For torsional vibration suppression, Shu et al (2014) studied the propagation of torsional wave in a thin circular plate of generalized PCs. Shu et al (2015) proposed a one-dimensional circular plate of piezoelectric radial phononic crystals and found the outer control gain has a significant effect on the torsional wave propagation. Fan et al (2019) designed a stack-like resonators consisting of periodically annular rubber, the finite element method (FEM) was used to study the longitudinal, torsional, and flexural vibration characteristics of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, compared with periodic structures, the Fibonacci (nonperiodic) structures can exhibit many unique dynamic behaviors. In our earlier work, stop band of torsional wave for the Fibonacci RPC [18] has been primitively investigated. However, few studies on transverse wave stop band can be found.…”
Section: Introductionmentioning
confidence: 99%